(untitled) (Economics and region, 2021)
Based on the analysis, the main problems and reasons for low efficiency and non-competitiveness of the Ukrainian economy, the decline of innovation, technology and economic potential of its enterprises were formulated. Improved mechanism for renovation and deep modernization of the domestic economy, first of all high-tech industrial and other enterprises, defines the main purpose, main tasks of National Innovative System development, methods and ways of their implementation were purposed in the article. The study formulates not only innovation and technological goals of production progress in Ukraine, but also identifies key moderators of national economy transformation and procedures for forming fundamental foundations for sustainable economic growth in the process of its development and adaptation to world standards of progress and competitiveness. The main points and procedure for the development and implementation of the National Strategy and Program of Innovative Development, procedures and tools for the implementation of "turnkey" of these strategic decisions are also proposed. The article lists the main sectors of the economy and industry of Ukraine, which should become the locomotives of innovation and technological progress of the state and its enterprises. The practical implementation of the conclusions and recommendations proposed in the study will contribute to the rapid transition of Ukraine to world standards of management, modern progress and ensure the competitiveness not only of the domestic economy but also of society as a whole.